Pertumbuhan Tunas Nenas Lokal Bangka Secara In-Vitro pada Media Murashige-Skoog dengan Penambahan Thidiazuron - Syafarudin, .; Widyastuti, Utut; Mustikarini, Eries Dyah; Rosa, Yanti (Universitas Bangka Belitung, 2010)
The aim is to find out the best combination of Murashige-Skoog (MS) media and Thidiazuron (TDZ) concentrations for promoting pineapple shoot growth. Planting material used in this research is a piece of axillar shoots from the Bangka local pineappleÂ that has been sub-cultured four times on media 2 mg/l BAP.Â Research used the completely randomized design in factorial that consists of 3 levels of MS media (50%,75% and 100%) combined with 4 levels of TDZ (2 mg/l BAP (control), 0.1 mg/l TDZ, 0.01 mg/l TDZ and 0.001 mg/l TDZ).Â Results showed that the use of 75% MS medium concentration gave the best effect on the variable of shoots appearing time (1.45 MST) and the shoots length (22.35 mm); the tabulation gives the highest average score on the variable number of shoots (6.44 shoots), explants percentage germination (97.22%) and number of leaves (8.6 pieces). The concentration of 0.01 mg/l TDZ gave the best effect of time for emerging shoots (1.51 MST) and the number of shoots (8.16 shoots). At concentrations 0.001 mg/l TDZ gave the best effect on the shoots length (28.07 mm) and number of leaves (11.12 pieces). The combination treatment of 75% MS medium and 0.01 mg/l TDZ provided the highest value for the time of emerging shoots (1.77 MST) and number of shoots at 8 MST (10.49 buds). The combination treatment of 75% MS medium with 0001 mg/l TDZ provided the highest value for the shoot length (31.22 mm) and number of leaves (11.88 pieces).